The Relationship Between Social Media Platform Usage and Sedentary Lifestyle Among Teenagers - Khansa, Aura; Sukaesih, Nunung Siti; Inriana, Ria (Inspirasi Foundation, 2026)
Introduction: The development of digital technology has driven increased social media use, particularly among teenagers. Increased access to social media has the potential to reduce physical activity levels and encourage a sedentary lifestyle. Objective: This study aims to analyze the relationship between the dominant social media platforms accessed and the level of sedentary lifestyle in adolescents at SMPN X Bandung City. Method: This research method used a quantitative correlational approach with a cross-sectional design. The sample was selected using a proportionate random sampling technique from students in grades VII, VIII, and IX. The instruments used were a self-report questionnaire to determine the dominant social media platform and the Adolescent Sedentary Activity Questionnaire (ASAQ) to measure the level of sedentary lifestyle. Data analysis was carried out using multiple linear regression tests using JASP software. Result: The results showed that the regression model was significant (F = 16.954; p < .001) with an R² value of 0.196, which means that 19.6% of the variation in sedentary lifestyle can be explained by the use of TikTok, Instagram, WhatsApp, and YouTube platforms. Partially, TikTok (p < .001) and YouTube (p = .005) significantly influenced sedentary lifestyle, with TikTok being the most dominant platform influencing sedentary lifestyle levels in adolescents. Meanwhile, Instagram (p = .081) and WhatsApp (p = .927) did not show a significant effect. Conclusion: This study concludes that certain social media platforms, particularly TikTok and YouTube, are associated with increased sedentary lifestyles in adolescents. These findings can be used as a basis for schools, parents, and health agencies in developing education and interventions to reduce sedentary lifestyles by regulating social media use more wisely.